Of Information Superhighways, Sexbots, Friends: The Delights of the Uncanny - Lemke, Cordula (Journal of Posthumanism, 2024)
This article explores the uncanny potential of artificial intelligence in view of the trope of the Frankensteinian creature. I argue that since Masahiro Mori has coined the term ‘uncanny valley’ the link that has been created between AI and the uncanny has more to do with postcolonial notions of first contact than with the uncanny as such. Reading Jeanette Winterson’s The Stone Gods, Spike Jonze’s Her and Kazuo Ishiguro’s Klara and the Sun, I investigate how these texts follow a new trajectory of AIs that are programmed to please rather than the well-trodden paths of dystopian or apocalyptic worst case scenarios. The AIs all raise important posthumanist issues that need addressing, but they do so in a very unthreatening manner. My final take on previous developments of a new medium shows that new mediums have mostly been denigrated as evil.